Adherence to a Mediterranean diet in Morocco and its correlates: cross-sectional analysis of a sample of the adult Moroccan population - El Rhazi Karima; Nejjari Chakib; Romaguera Dora; Feart Catherine; Obtel Majdouline; Zidouh Ahmed; Bekkali Rachid; Gateau Pascale (BMC, 2012)
Abstract Background Dietary habits in Morocco are changing and the causes are not well understood. This study aimed to analyse socio-demographic factors associated with adherence to the Mediterranean diet (MeDi) in a national random sample of the adult Moroccan population. Methods The data collected in this cross-sectional survey included socio-demographic factors and a food frequency questionnaire. MeDi adherence was assessed in 2214 individuals with complete dietary data. MeDi adherence was measured according to a simplified MeDi score based on the weekly frequency of intake of eight food groups (vegetables, legumes, fruits, cereal or potatoes, fish, red meat, dairy products and olive oil) with the use of the sex specific medians of the sample as cut-offs. A value of 0 or 1 was assigned to consumption of each component according to its presumed detrimental or beneficial effect on health. Logistic regression was used to estimate the association between MeDi adherence (low score 1-4 vs. high 5-8) and other factors. Results Mean age of the sample was 41.4 (standard deviation 15.3) years, 45.4% were men and 29.9% had a low MeDi adherence. Married subjects (adjusted odds ratio ORa=0.68, 95% CI 0.55-0.84) were less likely to have a low MeDi adherence compared to single, divorced or widowed persons. Persons from rural areas (ORa=1.46, 95% CI: 1.02-2.08), were more often low MeDi adherents compared to those from urban areas. Obese persons (ORa=1.56, 95% CI: 1.16-2.11) were more prone to low MeDi adherence than normal weight individuals. Conclusion MeDi is far from being a universal pattern in the Moroccan population. Intervention strategies should be implemented in target groups to maintain the traditional MeDi pattern considered as the original diet in Morocco.